The Kabylian Community: Towards a People Centred Socio-cultural Development - Touati, Redouane; Traxler, John (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2019)
This paper highlights ways of achieving socio-cultural development in Kabylian region in Algeria. This Amazigh (Berber) community has suffered much because of its mountainous geographical position and because of its marginalization by authorities for ideological reasons. These conditions or circumstances have reinforced the idea of self-reliance among members of this community and led to the emergence of the spirit of belonging, solidarity and cooperation amongst them. People depend on their culture and territory to organise themselves, to overcome their problems, and to develop their community. In fact, villagers are moving away from purely governmental development to people-centred development.